2021
DOI: 10.1186/s40644-021-00424-4
|View full text |Cite
|
Sign up to set email alerts
|

Clustering subtypes of breast cancer by combining immunohistochemistry profiles and metabolism characteristics measured using FDG PET/CT

Abstract: Background The aim of this study was to investigate the effect of combining immunohistochemical profiles and metabolic information to characterize breast cancer subtypes. Methods This retrospective study included 289 breast tumors from 284 patients who underwent preoperative 18 F-fluorodeoxyglucose (FDG) positron emission tomography/ computed tomography (PET/CT). Molecular subtypes of breast cancer were classified as Hormonal, HER2, Dual (a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
1
6
2
Order By: Relevance
“…The expression of HIF-1α, Glut-1 and Ki-67 correlated significantly with the 18 F-FDG uptake, which agreed with the findings of Bravatà et al. [42] , [43] , [44] . Together, these results suggested that RT can largely inhibit the growth of tumor tissues with a radiosensitizing effect in BRCA1 knockdown group, and this change can be dynamically monitored and assessed by the 18 F-FDG PET/CT imaging.…”
Section: Discussionsupporting
confidence: 90%
“…The expression of HIF-1α, Glut-1 and Ki-67 correlated significantly with the 18 F-FDG uptake, which agreed with the findings of Bravatà et al. [42] , [43] , [44] . Together, these results suggested that RT can largely inhibit the growth of tumor tissues with a radiosensitizing effect in BRCA1 knockdown group, and this change can be dynamically monitored and assessed by the 18 F-FDG PET/CT imaging.…”
Section: Discussionsupporting
confidence: 90%
“…An improved PET/CT model has previously been reported; the model determined the optimal cutoff value of the pSUVmax for each molecular subtype ( 19 ). This may be biologically plausible since several reports have elucidated the association between HER2 oncogene expression and 18F-FDG uptake ( 21 ), and pSUVmax was negatively correlated with the ER and PR ( 22 ). In this study, the optimal cutoff value of pSUVmax for each subtype was established by applying the receiver-operating characteristic curve analysis (cutoff values: luminal A-like type, 4.6; luminal B-like type, 4.8; luminal-HER2 type, 5.9; pure HER2 type 13.5; and triple-negative type, 7.9).…”
Section: Discussionmentioning
confidence: 84%
“…The authors found significantly higher SUV max values in the total population of TNBC patients and across subgroups by tumor size, grade, and stage, compared to the ERpositive/PR-positive/HER2-negative breast cancer group, suggesting increased tumor glycolysis may contribute to the aggressiveness of TNBC (70). Similarly, a retrospective study by Kwon et al studied pre-operative PET/CT scans of 284 newly diagnosed breast cancer patients (36 with TNBC) to correlate PET findings with histopathology, and found triple negative tumors to have significantly higher SUV values than other subtypes (71). Accordingly, in a prior prospective study by Garcia Vicente et al in 168 patients, SUV values in PET/CT scans obtained before neoadjuvant treatment correlated with molecular breast cancer subtype, with significantly higher SUV measures seen in HER2positive tumors and in the basal-like subtype, which is mostly comprised of TNBC (72).…”
Section: Characterization Of Tnbc Metabolism and The Immune Microenvi...mentioning
confidence: 99%
“…Similarly, a retrospective study by Kwon et al. studied pre-operative PET/CT scans of 284 newly diagnosed breast cancer patients (36 with TNBC) to correlate PET findings with histopathology, and found triple negative tumors to have significantly higher SUV values than other subtypes ( 71 ). Accordingly, in a prior prospective study by Garcia Vicente et al.…”
Section: Characterization Of Tnbc Metabolism and The Immune Microenvi...mentioning
confidence: 99%